Ekspektasi Pemegang Polis Generasi Y Dan Persepsi Dari Perusahaan Asuransi Kesehatan Di Jabodetabek - Ayu Diaztari; Bima Ardi; Derry Adhi; Wenny Priscillia; Yuricho Billy (Indonesian Business Review, 2018)
This research aims to know if there is any gap between expectations of the generation Y policy holders in Jabodetabek and their perceptions towards products and services from companies that the policy holders received. This research used SERVQUAL model toward Reliability, Assurance, Tangibility, Empathy, and Responsiveness. Subject population of this study is the Y generation who has health insurance policy. The sample are 130 person (92 male, 46 female). Researcher used SERVQUAL scores and also statistical description for analysis. The result found a gap exists between the expectations and perceptions from policyolders, where the expectations are higher than the perceptions.